2021
DOI: 10.1101/2021.01.20.21250195
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Integrating Operant and Cognitive Behavioral Economics to Inform Infectious Disease Response: Prevention, Testing, and Vaccination in the COVID-19 Pandemic

Abstract: The role of human behavior to thwart transmission of infectious diseases like COVID-19 is evident. Yet, many areas of psychological and behavioral science are limited in the ability to mobilize to address exponential spread or provide easily translatable findings for policymakers. Here we describe how integrating methods from operant and cognitive approaches to behavioral economics can provide robust policy relevant data. Adapting well validated methods from behavioral economic discounting and demand framework… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 77 publications
(106 reference statements)
0
7
0
Order By: Relevance
“…In an online RCT, doing so decreased vaccine hesitancy in strongly hesitant individuals [ 20 ]. Furthermore, in an online experiment (pre-print), participants were more likely to accept less effective vaccines if the development process took 12 rather than 7 months [ 32 ]. However, a message detailing the development process (pre-print) did not increase vaccination intention compared to no message in an online RCT in the US [ 22 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In an online RCT, doing so decreased vaccine hesitancy in strongly hesitant individuals [ 20 ]. Furthermore, in an online experiment (pre-print), participants were more likely to accept less effective vaccines if the development process took 12 rather than 7 months [ 32 ]. However, a message detailing the development process (pre-print) did not increase vaccination intention compared to no message in an online RCT in the US [ 22 ].…”
Section: Resultsmentioning
confidence: 99%
“…There was mixed effectiveness of framing on vaccination intention, although the evidence is limited. An online experiment (pre-print) found that positive framing of vaccine safety (95% safe) increased acceptance of less effective vaccines compared to negative framing (5% unsafe) [ 32 ]. On the other hand, an online RCT did not find a difference in intention when a news article framed vaccination protection against the virus negatively as opposed to positively [ 31 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…For instance, some hospitals use peer pressure to encourage vaccination (e.g., HCWs wearing "I am vaccinated" badges, public posting of vaccination rates) [48]. Pre-scheduling vaccination appointments or providing vaccination bonuses are promising evidence-based nudges to reach this group [49]. Additionally, messaging promoting prosocial motivations (e.g., protecting one's community from COVID-19) can enhance vaccination intentions in this group [50].…”
Section: Discussionmentioning
confidence: 99%